2018
DOI: 10.5194/acp-18-963-2018
|View full text |Cite
|
Sign up to set email alerts
|

Origin of elemental carbon in snow from western Siberia and northwestern European Russia during winter–spring 2014, 2015 and 2016

Abstract: Abstract. Short-lived climate forcers have been proven important both for the climate and human health. In particular, black carbon (BC) is an important climate forcer both as an aerosol and when deposited on snow and ice surface because of its strong light absorption. This paper presents measurements of elemental carbon (EC; a measurement-based definition of BC) in snow collected from western Siberia and northwestern European Russia during 2014, 2015 and 2016. The Russian Arctic is of great interest to the sc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 57 publications
0
31
0
1
Order By: Relevance
“…As a significant BC source, BB plays an especially important role in climate processes in the Arctic, where the increase of the annual surface temperature in the period since 1875 has been almost twice as large as that in the rest of the Northern Hemisphere (Bekryaev et al, 2010). Several studies (e.g., Shindell and Faluvegi, 2009;Flanner, 2013;Sand et al, 2015) have indicated that a significant part (up to about 50 %) of this temperature increase could have been induced by BC. There is an abundant amount of evidence that BB provides a significant contribution to BC in the Arctic atmosphere in the spring and summer (e.g., Stohl, 2006;Stohl et al, 2006;Warneke et al, 2010;Bian et al, 2013;Hall and Loboda, 2017;Popovicheva et al, 2017;Winiger et al, 2017;Qi et al, 2017;Xu et al, 2017;Evangeliou et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a significant BC source, BB plays an especially important role in climate processes in the Arctic, where the increase of the annual surface temperature in the period since 1875 has been almost twice as large as that in the rest of the Northern Hemisphere (Bekryaev et al, 2010). Several studies (e.g., Shindell and Faluvegi, 2009;Flanner, 2013;Sand et al, 2015) have indicated that a significant part (up to about 50 %) of this temperature increase could have been induced by BC. There is an abundant amount of evidence that BB provides a significant contribution to BC in the Arctic atmosphere in the spring and summer (e.g., Stohl, 2006;Stohl et al, 2006;Warneke et al, 2010;Bian et al, 2013;Hall and Loboda, 2017;Popovicheva et al, 2017;Winiger et al, 2017;Qi et al, 2017;Xu et al, 2017;Evangeliou et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…It has also been estimated that Siberian fires alone contributed almost half (46 %) of the total BC amount deposited in the Arctic over a period of 12 years (2002-2013). Radiative effects associated with BC residing in the Arctic atmosphere include both direct radiation budget changes causing strong warming of the Arctic surface and significant changes in atmospheric stability and cloud cover (Flanner, 2013;Sand et al, 2015). Significant increases in surface temperature in the Arctic as a result of perturbations of the meridional transport can even be caused by BC residing in the midlatitude atmosphere (Sand et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…3). For comparison, note that these values are almost three orders of magnitude lower than those of black carbon in Arctic snow 43,44 . It is seen that Northern Europe (e.g., Scandinavia), on one side, and North America on the other present higher snow concentrations than the Arctic.…”
Section: Concentrations Of Microplastics In Snow-covered Land and Icementioning
confidence: 96%
“…Land cover classification of burned areas are taken from the MODIS land cover change product (MOD12) (Friedl et al, 2010). This dataset is considered to be more realistic than GFED4 due to the emission factors used for BC (May et al, 2014) and the different approach to burned area calculation (see Hao et al, 2016).…”
Section: Bc Emissions In Northern Europementioning
confidence: 99%